Heroes and others: tensions and challenges in implementing Mentors in Violence Prevention in Swedish schools. (1st June 2020) - Bruno, Linnéa; Joelsson, Tanja; Franzén, Anna G.; Gottzén, Lucas
Abstract : This article explores the challenges that were detected in the first evaluation of the violence prevention programme Mentors in Violence Prevention at senior levels of compulsory schools and upper-secondary schools in Sweden. In particular, we analyse how the gender-transformative dimension and the bystander perspective aspect of the programme played out in the classroom. What are the implications of implementing a gender-transformative violence prevention programme such as Mentors in Violence Prevention when it is carried out by teachers in the school setting? The empirical basis for this study includes classroom observations during all seven Mentors in Violence Prevention sessions in two schools, and group interviews with a total of 14 teachers and 26 pupils (aged 13‐19) from five schools. Our findings suggest that most teachers did not appear to be comfortable with either the Mentors in Violence Prevention programme's pedagogical model or its theoretical approach. Consequently, they occasionally worked in manners contrary to the programme's intentions. However, observations and interviews demonstrated that a learning process about gender-based violence had been initiated. It may be necessary to make further adjustments if Mentors in Violence Prevention is to be used in schools in Sweden, particularly if teachers are to be the programme leaders.